Comparación de la prevalencia, severidad de caries y su relación con estilo de vida en institución educativa de la comuna 2 y 12 de Ibagué 2020 (2020)
This research is essential to establish the prevalence and severity of caries and its relationship with the lifestyle of the aforementioned population, since it aims to improve living conditions with respect to oral health, and sensitize parents, caregivers or caregivers on the presence of caries in infants to promote prevention as the most effective and economical means of maintaining oral health in children in the communities under study.